First year Health Psychology students perception of responsibility as a value in their professors - José Antonio Pomares Alfonso; Ana María Molina Gómez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
Background: as teachers are able to express in their conduct and relationships with the students values such as responsibility, love for their country and profession, honesty and sense of justice, among others, they will enhance their preparation as a learning motive. Objective: to assess the perception of first year Health Psychology students on their professor's responsibility value. Methods: a descriptive study conducted at the University of Medical Sciences of Cienfuegos in March, 2010 that included first year students of Health Psychology. Variables taken into account: attendance, punctuality, solidarity, respect for students and strictness. Results: 62, 5% of students assessed professor's attendance as very good and 12, 5% as fair. Punctuality reached 40, 6% as very good, 31, 3% as fair and 28, 1% as excellent. Over 50% considered respect towards students as very good, but over 30% regarded it was fair or poor. Over 80% answered from excellent to very good as to solidarity manifestations, but 12% answered fair or poor. About 30% of students have fair or poor perception professor's strictness. Conclusions: Although students' perception of professor's responsibility is generally positive, there are still negative aspects that may adversely influence the consolidation of this value in their own personality